TRANSFORMASI DIGITAL: WAJAH BARU PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KOTA YOGYAKARTA - Decky Setiawan Putra; Selo Selo; Silmi Fauziati (Universitas Janabadra, 2021)
Public services are one of the sectors affected by the Covid-19 pandemic. Restrictions on face-to-face access to public services force the digital transformation process to take place. This study aims to provide information about the digital transformation that occurs in civil administration services in the city of Yogyakarta. The method used is a case study at the Yogyakarta City Population and Civil Registration Service. There are three types of digital transformation in civil administration services in Yogyakarta City, namely changes in service patterns, changes in civil administration files, and the use of Electronic Signatures (TTE). It can be concluded that digital transformation in civil administration services in Yogyakarta City is able to meet the needs of public services during the Covid-19 pandemic. The thing of concern is the uneven level of Information Technology literacy in the community as well as concerns about the privacy and security of digital data in connection with the use of social media as a means of digital transformation in civil administration services in Yogyakarta City.Keywords: Covid-19, Digital Transformation, Public Service, E-Government